Chronic tendo-Achilles ruptures treated by suture anchor repair and augmentation with flexor hallucis longus tendon transfer, fixed with ACL screw - Ramesh, B.; Basha, Shaik Azam; Mylapalli, Vishal Bhargav; Panda, Kirtan Ram; Poola, Sai Kiranmai (International Journal of Research in Orthopaedics, 2025)
Different surgical procedures have been used for treatment of chronic ruptures of the Achilles tendon with varying results. This study assesses the functional outcomes and complications of chronic insertional tears of Achilles tendon. 10 patients with chronic ruptures of the Achilles tendon were followed for a mean period of 10.3 months. Only ruptures at or near (within 1 cm) insertion were included. They were treated by direct repair of tendon to calcaneum by suture anchor. Flexor hallucis longus (FHL) tendon transfer fixed to calcaneal tunnel with an interference screw was used to augment the repair. Outcome was assessed by AOFAS Ankle-Hindfoot (AHS) score. The mean preoperative score of 41.2 improved to 85.4 at final follow-up out of a total 100 points. We achieved excellent results in 80% and good outcome in 20% cases. No re-ruptures were noted. In insertional chronic ruptures of Achilles tendon, FHL transfer to calcaneum with interference screw fixation and repair of Achilles tendon with suture anchor is a reliable technique with good outcome and is recommended.